Artikel Review : Uji Stabilitas Sediaan Parenteral Volume Besar - Sintya (PC Ikatan Apoteker Indonesia (IAI) Karanganyar, 2025)
Large-volume parenteral preparations are sterile preparations for intravenous use that must meet strict quality requirements, especially regarding stability, sterility, and clarity. This review article aims to examine stability testing and quality evaluation of parenteral preparations based on formulation aspects, manufacturing technology, and aseptic practices. The method used was a literature study of scientific articles published in the last 10 years. The results of the review show that formulation technologies such as the use of cosolvents, lyophilization, and cyclodextrin inclusion complexes can improve the stability and quality of parenteral preparations. However, process inconsistencies and suboptimal aseptic practices can reduce the quality of preparations even though some physicochemical parameters meet the standards. Therefore, process control and consistent application of aseptic practices are important factors in ensuring the safety and efficacy of large-volume parenteral preparations.